"Making Literature Hum": Canadian Literary Journalism in the Twenties - Chittick, Kathryn (Studies in Canadian Literature, 1981)
The attempt of the Twenties to find for Canadian writers a ground somewhere between narcotic and arcane literature failed. The Canadian Bookman and the Canadian Authors Association, representing Canadian authors at the beginning of the modern era, failed to effect the looked-for revolution in Canadian literature; the Canadian authors, now at the end of modernism, seem likely once again to fossilize the achievements of the past quarter century in the mire of self-congratulation. The Canadian reading public is left to be mystified by the spectacle. There is perhaps cause left for optimism in the very fact of national cultural review, as yet again a forum is created for the meeting of authors, publishers, and critics. This time, too, the narcotic Media have been summoned to the reckoning of Canadian culture. But it is not so certain that this is to be an era of ideas.